2006
DOI: 10.1007/s11267-005-9023-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical immobilisation of arsenic in contaminated soils using iron(II)sulphate—advantages and pitfalls

Abstract: Chemical immobilisation of inorganic contaminants by increasing the sorption capacity of soils and/or promoting the formation of sparingly soluble precipitates may be a cost-effective approach to counteract groundwater pollution. This study focuses on the enhanced retention of arsenic in two contaminated soils by addition of solid iron(II)sulphate. Four lab-scale column experiments were performed under unsaturated conditions with subsoil material sampled at a former timber preservation site and a pigment produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…They reported that water-extractable As in Feamended soil was reduced from 459 to 40 lg kg -1 . Gemeinhardt et al (2006) reported from a column test that up to 90% of leachable As in Fe-amended soil was immobilized. Also, the addition of Fe-halide salts to contaminated soils decreased the bioaccessibility of As in a physiologically based extraction test (Subacz et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that water-extractable As in Feamended soil was reduced from 459 to 40 lg kg -1 . Gemeinhardt et al (2006) reported from a column test that up to 90% of leachable As in Fe-amended soil was immobilized. Also, the addition of Fe-halide salts to contaminated soils decreased the bioaccessibility of As in a physiologically based extraction test (Subacz et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the mobility of As in soil by the addition of amendments has mostly been evaluated via chemical distribution from sequential extraction tests (Gemeinhardt et al 2006). Although this approach has some advantages, such as simple and rapid decisions, it does not provide useful information on As toxicity with respect to soil biological quality as a result of changes in soil enzyme activities ), which have previously been used as good indicators for predicting the changes in the soil quality and biological toxicity due to As (Dick 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic in soils is sorbed mainly onto surfaces of clay minerals and Fe, Al, and Mn oxides (Jain and Loeppert, 2000;Grafe et al, 2001;Goldberg, 2002;Kinniburgh and Cooper, 2004). Solubility-controlling mineral phases are Mn arsenates (Tournassat et al, 2002), Ca arsenates (Bothe and Brown, 1999), and Fe oxides, e.g., scorodite or arsenopyrite (Thornburg and Sahai, 2004;Gemeinhardt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of Fe(II), as single step treatment, has already been proposed to remediate As and Cr contaminated soils (Moore et al, 2000;Warren and Alloway, 2003;Gemeinhardt et al, 2004) showing that FeSO 4 can greatly reduce mobility and plant availability of As and Cr. Hartley et al (2004), testing different forms of Fe treatments added to three As contaminated soils, found that Fe(II) and Fe(III) were the most effective at reducing the concentration of As in leachates.…”
mentioning
confidence: 99%
“…No explanation for this phenomenon was given. Also Warren and Alloway (2003) and Gemeinhardt et al (2004) observed a significant increase in toxic metal solubility after Fe(II) additions, but attributed it to insufficient lime application and/or to a temporary drop in soil pH. To date, there have been no studies on the potential of multiple FeSO 4 additions to reduce the availability and mobility of metals in contaminated soils.…”
mentioning
confidence: 99%